Host identity, more than elevation, shapes bee microbiomes along a tropical elevation gradient - Pinos, Andrea; Alonso-Alonso, Pedro; Correa-Carmona, Yenny; Holzmann, Kim L.; Yon, Felipe; Brehm, Gunnar; Steffan-Dewenter, Ingolf; Peters, Marcell K.; Weinhold, Arne; Keller, Alexander (Frontiers in Microbiology, 2025)
Understanding how host-microbiome interactions respond to abiotic and biotic factors is key to elucidating the mechanisms influencing ecological communities under current climate change scenarios. Despite increasing evidence that gut microbial communities associated with bees influence their health and fitness, including key roles in nutrient assimilation, toxin removal, defense against pathogens, and immune responses, the distribution of gut microbial communities and the dynamics of these associations along environmental gradients remain poorly understood. In this study, we assessed how environmental changes with elevation and host taxonomic identity influence the bacterial gut microbiome of wild bees collected along a 3,600 m elevation gradient in the Peruvian Andes. We applied DNA metabarcoding on the 16S rRNA region of gut samples from five bee tribes: Apini (honey bees), Bombini (bumble bees), Meliponini (stingless bees), Euglossini (orchid bees), and Halictini (sweat bees). Our findings indicate a general decrease in bacterial diversity and a high turnover of microbial taxa along the elevation gradient, with notable differences among host tribes. Host taxonomic identity was a strong predictor of gut microbial community composition, despite a high turnover of microbial and host taxa along the gradient. Within tribes, the turnover of microbial compositions was mainly explained by environmental changes with elevation in bumble and stingless bees. The observed variations in gut microbial diversity and composition at different elevations and different host taxa suggest that both factors significantly impact the gut microbiomes. As climate change continues to influence environmental conditions in the Andean-Amazonian forests it is crucial to consider how these changes may affect host-microbiome relationships. This highlights the necessity of understanding both abiotic and biotic factors in the context of climate change.